Application of Natural Betalain Dye from Beetroot for Improved Efficiency in Dye Sensitized Solar Cell. Issue 1 (September 2021) - Soni, K; Sheikh, A; Jain, V; Lakshmi, N
Abstract: C, N, S co-doped TiO2 (TU-TiO2 ) synthesized through solid state method using high energy ball milling was applied onto fluorine doped tin oxide (FTO) glass substrate and sintered at 450° C for half hour for use as a photoanode of dye-sensitized solar cells (DSSCs). Natural Betalain containing dye extracted from beetroot was used as sensitizer, Iodide triodide was used as electrolyte and graphite as counter electrode to obtain FTO/C, N, S-TiO2 /Dye/Electrolyte/Graphite/FTO DSSC. X-ray Diffraction analysis established the formation of single phased materials retaining the basic TiO2 structure. Optical properties were enhanced with increase in molar concentration of thiourea in TiO2 . Fourier Transform Infrared spectroscopy confirmed the incorporation of sulphur into TiO2 . The highest of 94% relative increase is observed in solar to electric conversion efficiency for C, N, S co-doped TiO2 compared to un-doped TiO2 . Along with decrease in the band gap making the cell more sensitive to visible light, the improved performance is also due to the rise in charge injection from betalain dye to the C, N, S co-doped TiO2 .